This study aims to identify the effectiveness of the life skills program on the self-concept and optimism of people with learning difficulties. The researcher adopted an experimental approach. The study sample consisted of 70 male and female students from (Journal Of Educational and Psychological Researches, 2024)
This study aims to identify the effectiveness of the life skills program on the self-concept and optimism of people with learning difficulties. The researcher adopted an experimental approach. The study sample consisted of 70 male and female students from schools in the city of Arar, in the northern border region of the Kingdom of Saudi Arabia. The results showed a clear impact on the study sample, resulting in increased confidence and an increase in self-concept and optimism. The results also showed a positive correlation between life skills, self-concept, and optimism.